UPAYA PENINGKATAN DIVERSIFIKASI KONSUMSI PANGAN MELALUI PENGEMBANGAN PRODUK PANGAN OLAHAN: KASUS PADA KOMODITAS JAGUNG DAN SAGU - Ariningsih, Ening; Ariani, Mewa (Indonesian Journal of Socio Economics)
Staple food consumption pattern which was traditionally various, has shifted toward single staple food pattern, that is rice.  Meanwhile, there are still few people who consume corn and sago, but their consumption level are still low.  The objective of this study is to analyze various corn and sago-based processed food as an effort to promote food consumption diversification.  This study employed both secondary and primary data, collected from NTT and Papua Provinces which were purposively chosen as case study locations.  Province of NTT is for corn consumption whereas Papua for sago.  The data collected were analyzed qualitative-descriptively using  tables and diagrams.  The study suggests that maize and sago could be used as raw materials in various processed food, which are manufactured by both large and medium industries, and small and household industries.  Henceforth, it is clear that the development of maize and sago based food industries must be conducted continuosly as an effort to promote food consumption diversification.